HUBUNGAN MINAT BELAJAR DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS XI SEMESTER II SMAK ST. PETRUS ENDE - Yunita Rendang; Maria Goreti Diciloam Bantas; Yasinta Yenita Dhiki (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
This study aims to determine the relationship between interest in learning and learning achievement in mathematics in Class XI Semester II SMAK St. Petrus Ende. The approach used is a quantitative approach. Data analysis used the product moment formula with a significance level of 5%. The results of the study showed (1) the learning interest of Class XI Semester II students of SMAK St. Petrus Ende is known to be in the 33,33% trend category of high, (2) Mathematics learning achievement of Class XI Semester II students of SMAK St. Petrus Ende is known to be in the category of high tendencies of 33%, (3) From the results of the analysis, the sig value is obtained. (2-tailed) 0.000 <0.05 with a Pearson Correlation score of 0.699 so it can be concluded that there is an influence between learning interest and learning achievement in mathematics in class XI students in the second semester of SMAK St. Petrus Ende. Furthermore, the coefficient of determination was tested to see the magnitude of the influence of interest in learning on learning achievement in mathematics and obtained a coefficient of determination of 0.489/48,9%. So it can be concluded that Ho is rejected and Ha is accepted, meaning that there is a relationship between interest in learning and learning achievement in mathematics for Class XI Semester II SMAK St. Petrus Ende. Thus, it is suggested, (1) For schools, it can be used as material for teacher consideration in carrying out the learning process at school (2) For mathematics teachers, it can find out students' interest in learning.